Evaluación de insecticidas biorracionales para el control de las principales plagas del chocho (Lupinus mutabilis) en la Universidad Técnica de Cotopaxi “Campus Salache” del Cantón Latacunga. - Camalle Chiliquinga, Blanca Melida (2018)
Evaluation of organic insecticides to control the primary plague of chocho (Lupinus mutabilis) in the Technical University of Cotopaxi, Salache Campus, Latacunga Canton. The objectives of this study were i) to select the best insecticide to control the main plagues of chocho ("barrenador," cutworm, bedbug, and thrips) and ii) to report the cost of the treatments. To address these objectives, experiments were set up in a randomized complete block design (RCB) with eight treatments, each treatment with three biological replicates, giving a total of twenty-four experimental units in an area of 1,598 m2. Statistical analyses of the data were performed using InfoSat (IS) statistic software to the variable ‘insecticide’ on the percentage of plague control the changing analysis ANOVA. The results of this study reveal that T8 (Decis) was significantly different compared to other treatments, except T4 (garlic + chili) that showed similar results to T8 although with a slight, but not a statistically significant difference between them. The presence of the plague after application of T8 (Decis) was 3,87% low "barrenador" (Díptera agromyzidae), 3,23% "barrenador" tip of the stem (Díptera anthomyzidae), 3,33% cutworms (Agrotys sp),2.93% bedbug (Rhinocloa sp), 1,67% flower thrips (Frankiniella sp). The effect of T8 treatment in controlling the plague is attributed to the pyrethroid insecticide ‘Deltamethrin,’ after its ingestion, Deltamethrin disrupts the insect’s nervous system with lethal results. However, due to the similar effects found between T8 and T4, this result suggests that T4 (garlic + chili) can be used instead of T8. Both T8 and T4 were efficient in controlling insect plague, but T4 which is an organic insecticide and more environmentally friendly can be used as a natural control with a worthwhile cost to farmers.